Reform of Civil Servant Pension Benefits Implementation Regulations in the Theory of Law and Development - Sitepu, Dila Kristy Br. (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The implementation of Civil Servant Pension Benefits is currently run by PT TASPEN (Persero) since 1987. Payment of Civil Servant Pension Benefits is given monthly for the continuity of old age income as a right and as a reward for the dedication of Civil Servants, as well as the fulfillment of sustainable economic, social and cultural rights and guarantees of a decent life in accordance with duties, responsibilities and obligations. However, with the issuance of Law Number 20 of 2023 concerning the State Civil Apparatus, a new Paradigm has been created regarding the implementation of Civil Servant Pension Benefits. In accordance with Article 22 paragraph (3) and Article 23 of Law Number 20 of 2023 concerning the State Civil Apparatus which states that "Old Age Security and ASN Pension Security are provided in a social security program in accordance with the national social security system and the social security administering body". This causes uncertainty about the future of the "Old Age Program and Pension Program" which has been organized by PT TASPEN (Persero), which has provided financial benefits for Civil Servants. The normative method is used in conducting a study on the Study of the Implementation of Civil Servant Pension Benefits in the Theory of Development Law, there are 3 (three) approaches to studying the problem, namely the legislative approach (statue approach), case approach (case approach), as well as conceptual approaches (conceptual approachThe pension system is a legal instrument directly related to fiscal policy, social protection, and personnel management. Therefore, pension reform must be designed comprehensively and in stages. Development Law Theory provides the basis for pension law reforms to strengthen civil servant governance to support the achievement of national development goals.